Surgery experiences of patients with hematologic cancer, individual applications for the symptoms due to chemotherapy and determination of the anxiety levels - Yiğit, Gülcan; Aygin, Dilek (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The aim of the study was to determine the surgical experiences of patients with hematologic cancer, their anxiety levels, and their individual practices regarding the symptoms they experience. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study was conducted by face-to-face interviews with 74 patients followed up in a hematology clinic. The “Patient information form” and “Beck Anxiety Scale” were administered to the patients before chemotherapy, and the “Questionnaire Form Including Patients Practices for Symptoms” was administered after chemotherapy. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The mean age of the participants was 63.76±15.1 years, 47.3% were female, 47.3% were diagnosed with lymphoma, 67.6% had undergone surgery, and 32% received education. The mean Beck Anxiety Scale score was 11.36±7.99 and was considered mild anxiety. A significant difference was observed between education and employment status and postoperative education status, gender and hair loss, employment status and anorexia, scale score and employment status, and the effect of COVID-19 on chemotherapy (p<0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. It was determined that patients with hematological cancer had a low levels of knowledge about surgical procedures and they did not perform any negative practice due to chemotherapy. Their anxiety levels were mild and the pandemic process was effective on anxiety.